(untitled) (Biological Sciences - PJSIR, 2003)
A tridentate Schiff base C H N O having ONN donor sequence has been synthesised from the condensation of 1.6- 13 20 2 diaminohexane with salicylaldehyde. Several new thiocyanato complexes of Cu (II), Pd (II), Ti (III) and V(IV) containing the above ligand have been synthesised and characterized by elemental analyses, conductivity, magnetic measurements, IR and NMR spectra and electronic spectroscopic studies. Magnetic and spectral data support the octahedral geometries for Ti (III) and V(IV) complexes, whereas Cu(II) and Pd(II) complexes are square-planar in nature.